Resistência de porta-enxertos e híbridos de tomateiro à Ralstonia solanacearum - Busato, Laedio Magno (2017)
Faced with the great need to develop techniques that potentiate the production of food free of chemicals to meet the great pressure of the world society for healthier foods and due to the increased use of grafting techniques in agricultural production, Th